Optimal designs in plant breeding experiments: a simulation study using wheat pedigree matrix - Ribeiro Santos, Paula; Alcarde Sermarini, Renata (Brazilian Journal of Biometrics, 2025)
Plant breeding programs involve the selection of new superior lines. However, for a large number of test lines, there are several limitations in the use of certain designs. Therefore, the success of these programs depends on an adequate experimental design that allows obtaining accurate estimates of genetic effects, increasing the efficiency of the experiment and controlling experimental variability. In addition, considering the dependence between genetic effects is desirable to ensure the validity and generalization of results, avoiding biased estimates and incorrect interpretations. To this end, using partially replicated designs (p-rep), in which a percentage, p, of test lines are replicated and the others not, can be a good option. Thus, a simulation study was conducted to evaluate designs for early phase wheat breading experiments according to the optimization criterion C, considering the dependence or independence between test lines, comparing them in relation to the perceived genetic gain and, consequently, the quality of the material selection, for a given experimental area and for p = 20%, for different genetic variance values. It could be concluded that the differences between designs are small, and that they are more affected by the magnitude of the genetic variance assumed for data.